Proposed protocol for management of acute burn during COVID19 outbreak: An Indian Perspective - Shammi Purwar; Shesh Kumar; Poonam Gupta (International Journal of Health and Clinical Research, 2021)
The burn department of any hospital is an emergency department which faces serious threats for infection. As the burn patients have compromised immunity,any new patient admitted in the burn ward may be a potential source of COVID19.So, it becomes very necessary to manage the whole process including triage , admission ,management of burn ICU (BICU) ,surgeries, physiotherapy, discharge and rehabilitation.COVID19 pandemic is presently affecting each and every country of the world including India. The epidemic was first reported from Wuhan in Hubei province of China in December 2019.The pandemic is caused by 2019-CoV.This paper proposes some strategies and suggestions regarding the effective management of burn patients at every stage based on our experiences (at UPUMS Hospital,Saifai).